Surgical Techniques and Outcomes in Patients With Intra-Cardiac Abscesses Complicating Infective Endocarditis - Straw, Sam; Baig, M. Wazir; Mishra, Vishal; Gillott, Richard; Witte, Klaus K.; Van Doorn, Carin; Ferrara, Antonella; Javangula, Kalyana; Sandoe, Jonathan A. T. (Frontiers in Cardiovascular Medicine, 2022)
Background An intra-cardiac abscess is a serious complication of both native (NV-IE) and prosthetic valve infective endocarditis (PV-IE). Despite being an accepted indication for surgery, controversies remain regarding the optimal timing and type of operation. We aimed to report the outcomes of patients managed for intra-cardiac abscesses over more than a decade. Methods Patients aged ≥18 years managed for intra-cardiac abscess between 1 January 2005 and 31 December 2017 were identified from a prospectively collected IE database. The primary outcome was 30-day mortality in operated patients and secondary outcomes were freedom from re-infection, re-operation and long-term mortality comparing those patients with aortic root abscess who underwent aortic valve replacement (AVR) and those who received aortic root replacement (ARR). Results Fifty-nine patients developed an intra-cardiac abscess, and their median age was 55 (43–71) years; among them, 44 (75%) were men, and 10 (17%) were persons who injected drugs. Infection with beta-haemolytic streptococci was associated with NV-IE (p = 0.009) and coagulase-negative staphylococci with PV-IE (p = 0.005). Forty-four (75%) underwent an operation, and among those with aortic root abscess, 27 underwent AVR and 12 ARR. Thirty-day mortality was associated with infection with S. aureus (p = 0.006) but not the type or timing of the operation. Survival in operated patients was 66% at 1 year and 59% at 5 years. In operated patients, none had a relapse, although six developed late recurrence. Freedom from infection, re-operation and long-term mortality were similar in patients undergoing AVR compared to ARR. Conclusion Patients diagnosed with intra-cardiac abscess who were not operated on had very poor survival. In those who underwent an operation, either by AVR or ARR based upon patient factors, imaging and intra-operative findings outcomes were similar.